Anisotropic distortion in the perceived orientation of stimuli on the arm - Scinob Kuroki (Nature Portfolio, 2021)
Abstract Mechanoreceptors on the skin are heterogeneously distributed, and the sampling of neural signals in the brain can vary depending on the part of the body. Therefore, it can be challenging for the brain to consistently represent stimuli applied to different body sites. Here, we report an example of a regional perceptual distortion of the tactile space. We used a piezoelectric braille display to examine shape perception on the volar surface of the arm and to compare it to that on the palm. We found that the orientation of perceived stimuli on the arm was distorted in certain areas. In particular, an inwardly-inclined line shape was perceived as being more inwardly-inclined than it actually was. On the other hand, an outwardly-inclined line was perceived accurately. When the same stimuli were applied to the palm, this anisotropic bias was not observed. We also found that changing the posture of the arm changed the angle at which this anisotropic distortion occurred, suggesting the influence of the skin frame of reference on this illusion. This study showed a clear example of how the representation of even simple stimuli is complexly distinct when the stimuli are applied to different body sites.